Mitochondrial-Nuclear Interactions Mediate Sex-Specific Transcriptional Profiles in Drosophila. Issue 2 (1st October 2016) - Mossman, Jim A; Tross, Jennifer G; Li, Nan; Wu, Zhijin; Rand, David M
Abstract: The assembly and function of mitochondria require coordinated expression from two distinct genomes, the mitochondrial DNA (mtDNA) and nuclear DNA (nDNA). Mutations in either genome can be a source of phenotypic variation, yet their coexpression has been largely overlooked as a source of variation, particularly in the emerging paradigm of mitochondrial replacement therapy. Here we tested how the transcriptome responds to mtDNA and nDNA variation, along with mitonuclear interactions (mtDNA × nDNA) in Drosophila melanogaster . We used two mtDNA haplotypes that differ in a substantial number of single nucleotide polymorphisms, with >100 amino acid differences. We placed each haplotype on each of two D . melanogaster nuclear backgrounds and tested for transcription differences in both sexes. We found that large numbers of transcripts were differentially expressed between nuclear backgrounds, and that mtDNA type altered the expression of nDNA genes, suggesting a retrograde, trans effect of mitochondrial genotype. Females were generally more sensitive to genetic perturbation than males, and males demonstrated an asymmetrical effect of mtDNA in each nuclear background; mtDNA effects were nuclear-background specific. mtDNA-sensitive genes were not enriched in male- or female-limited expression space in either sex. Using a variety of differential expression analyses, we show the responses to mitonuclear covariation to be substantially different between the sexes, yet the mtDNA genes were consistently differentially expressed across nuclear backgrounds and sexes. Our results provide evidence that the main mtDNA effects can be consistent across nuclear backgrounds, but the interactions between mtDNA and nDNA can lead to sex-specific global transcript responses.